Case report: solitary splenic metastasis occurring 19 months after primary treatment for occult breast cancer - Chen, Yuanqi; Zhang, Liulu; Sun, Taotao; Cheng, Min-Yi; Zou, Jiachen; Wang, Kun (Frontiers in Oncology, 2022)
Occult breast cancer, commonly presenting with axillary lymphadenopathy, is an extremely rare entity of breast cancer. Metastasis to the spleen as a single site is rarely seen and has been little reported in literature. Herein, we described a case of a 60-year-old patient presented with an asymptomatic solitary splenic mass 19 months after axillary lymph node dissection, regional radiotherapy and systemic therapy. Laparoscopic splenectomy was performed and histopathological examination confirmed metastasis from occult breast cancer. Then the patient was administered oral vinorelbine and dual-targeted treatment. With over 10 months of follow-up, there is no evidence of recurrence or metastasis of malignancy. To our knowledge, this study reports the first case of solitary splenic metastasis from occult breast cancer and highlights the importance of considering splenic metastasis as the only site of recurrence during follow-up of primary cancer, regardless of its rarity. If possible, splenectomy may be a therapeutic strategy.